Identification of a Novel, Invasive, Not-Yet-Cultivated Treponema sp. in the Large Intestine of Pigs by PCR Amplification of the 16S rRNA Gene - Mølbak, Lars (American Society for Microbiology, 2006)
Laser capture microdissection in combination with fluorescent in situ hybridization was used to identify an unknown species of spirochetes from the pig colonic mucosa. The 16S rRNA gene was PCR amplified, and the closest related type strain was Treponema bryantii(T) (90.1%). The spirochete, here named “Candidatus Treponema suis,” was associated with colitis, including invasion of the surface epithelium as well as superficial parts of the mucosa.